Strategi Belajar dalam Motivasi Membaca Siswa - Iqlima, Fairisa (Lembaga Yasin AlSys, 2024)
In Indonesia, there are still many people who read minimally. There are several factors that cause the lack of reading in Indonesia. The purpose of this research is to analyze the influence of reading interest on learning outcomes, analyze the influence of learning motivation on learning outcomes, and analyze the influence of reading interest and learning motivation on student learning outcomes. Reading activities among school students are still not optimal, students' reading enthusiasm is still very low. Teachers' awareness of students' reading motivation is also still low. This type of research uses qualitative, this research uses research analysis techniques and case studies in journals. It cannot be denied that low interest in reading is a problem that deserves attention. To overcome this problem, we must be able to do something simple by realizing that reading is very important, and we must also implement our reading culture.